Investigating the impact of regiochemistry in ester functionalized polyfurans. Issue 3 (20th September 2021) - Varni, Anthony J.; Kawakami, Manami; Kramer, Stephanie N.; Rice, Megan; Geib, Steven J.; Peteanu, Linda A.; Kowalewski, Tomasz; Noonan, Kevin J. T.
Abstract: In this study, the impact of ester side group regiochemistry on electronic and conformational properties of regioregular polyfurans was explored. A derivative with alternating head‐to‐head and tail‐to‐tail orientation of the side groups was synthesized and compared with its head‐to‐tail analogue, and these were benchmarked against the related regioregular poly(3‐hexylfurans). The study revealed that alkyl ester side groups in a head‐to‐head orientation will create significant steric strain as compared with linear alkyl chains with identical regiochemistry. Though the head‐to‐head ester side groups lead to twisting along the polymer backbone, they also produce a protective effect against photodegradation in comparison with a poly(3‐hexylfuran). Altogether, the work highlights how side groups can impact conformational properties and stability of polyfurans. Abstract :